Using clonidine in the treatment of tizanidine abuse and withdrawal: a case report of a patient with somatoform pain disorder. (2nd September 2020) - Kitta, Anna; Wippel, Andreas; Richwien, Paula; Prager, Gerhard; Adamidis, Feroniki; Masel, Eva Katharina; König, Daniel; Ossege, Michael; Berger, Peter
ABSTRACT: Tizanidine is a noradrenergic alpha-2 receptor agonist approved in the treatment of muscle spasticity. Limited data on abuse and withdrawal of Tizanidine are available. We present a case of severe withdrawal and symptoms of psychological and physiological dependence: A 52-year-old woman who was transferred to the psychosomatic unit because of pain and anxiety. She presented with a long history of inpatient treatment due to symptoms of pain. After multiple treatment options had been tried without much efficacy, the patient was prescribed Tizanidine for her symptoms of pain. As symptoms were diminished, treatment was upheld. Soon, abuse, and later, dependence of Tizanidine had established. At time of admission, the patient had been on a self-escalated daily administration scheme of 40 mg of Tizanidine. As dose tapering proved unsuccessful, dose reduction with Lorazepam to reduce withdrawal symptoms was attempted. As also the additive treatment with Lorazepam showed no satisfying results, another treatment option was needed. After establishing Clonidine, the off tapering of Tizanidine was much better tolerated by the patient and finally proved successful. This case report draws attention to possible severe abuse of Tizanidine and the major clinical aspects and challenges in the treatment of Tizanidine withdrawal.